2016
DOI: 10.1002/jcp.25507
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte Morphology in Stiff and Soft Agarose Gels and the Influence of Fetal Calf Serum

Abstract: Changes to chondrocyte volume/morphology may have deleterious effects on extracellular matrix (ECM) metabolism potentially leading to cartilage deterioration and osteoarthritis (OA). The factors controlling chondrocyte properties are poorly understood, however, pericellular matrix (PCM) weakening may be involved. We have studied the density, volume, morphology, and clustering of cultured bovine articular chondrocytes within stiff (2% w/v) and soft (0.2% w/v) three-dimensional agarose gels. Gels with encapsulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 61 publications
(80 reference statements)
2
26
0
Order By: Relevance
“…), as its depletion around chondrocytes could provide a weak area into which process(es) could develop. For example, chondrocytes cultured in soft, as opposed to stiff, agarose gels produce cytoplasmic processes with similar structures to those described in the present study (Karim & Hall, ). Alternatively, the development of processes could result from mechanically injured chondrocytes leading to an ‘active’ metabolic response and resulting in the release of cytokines/degradative enzymes and breakdown of the pericellular matrix.…”
Section: Discussionsupporting
confidence: 82%
“…), as its depletion around chondrocytes could provide a weak area into which process(es) could develop. For example, chondrocytes cultured in soft, as opposed to stiff, agarose gels produce cytoplasmic processes with similar structures to those described in the present study (Karim & Hall, ). Alternatively, the development of processes could result from mechanically injured chondrocytes leading to an ‘active’ metabolic response and resulting in the release of cytokines/degradative enzymes and breakdown of the pericellular matrix.…”
Section: Discussionsupporting
confidence: 82%
“…CLSM studies on fluorescently-labelled chondrocytes show similar processes also occasionally present after 7 days in stiff (2%) 3D agarose cultures containing FCS. However, their incidence rises markedly in soft (0.2%) agarose gels [ 42 ]. It is possible that the penetration of the growth/mitogenic factors in FCS into cartilage and stiff gels is severely restricted, but when the matrix or gel is weakened (by scalpel injury or culture in soft agarose gel) these factors can penetrate and stimulate chondrocyte morphological changes.…”
Section: A New Look At Cartilage—imaging In Situ Fluorescently-labellmentioning
confidence: 99%
“…Importantly, as viability is expressed as a percentage, this does not necessarily indicate an increase in cell number, rather a change in the ratio of live: dead cells present. A potential reason for this could be the presence of enzymes in the foetal bovine serum present in supplemented growth medium that can act to digest dead cellular DNA and therefore alter the dead cell ratio found through the quantitative assessment [ 36 , 37 ]. This was investigated over a period of 4 days with no significant effect (data not shown) but remains to be a potential factor that was influencing these cell populations.…”
Section: Resultsmentioning
confidence: 99%
“…9B ). Agarose has been used as a 3D scaffold before [ 36 ] and other studies have reported conflicting reports about cell viability in agarose. Ise et al reported an increase in hepatocytes proliferation and viability after 21 days of culture when encapsulate in 3% agarose [ 38 ].…”
Section: Resultsmentioning
confidence: 99%